Sulfated Zirconia: An Efficient and Reusable Heterogeneous Catalyst in the Friedel-Crafts Acylation Reaction of 3-Methylindole - Vargas, Darío Andrés (2017)
An efficient process for the Friedel–Crafts acylation of 3-methylindole with acid anhydrides in the presence of sulfated zirconia was developed. This catalyst shows excellent catalytic activity with good conversion and selectivity towards formation of the products of 2-acylation (3-methyl-1H-indol-2-yl)ketones. Other advantages related to this process are the simple work-up procedure and smaller production of chemical waste. The catalyst was easily recycled and reused with a minimal loss in activity through three reaction cycles. The catalyst was characterized by FT-IR spectroscopy, X-Ray diffraction and superficial acidity.